2022
DOI: 10.3390/pharmaceutics14030525
|View full text |Cite
|
Sign up to set email alerts
|

Iontophoresis of Biological Macromolecular Drugs

Abstract: Over the last few decades, biological macromolecular drugs (e.g., peptides, proteins, and nucleic acids) have become a significant therapeutic modality for the treatment of various diseases. These drugs are considered superior to small-molecule drugs because of their high specificity and favorable safety profiles. However, such drugs are limited by their low oral bioavailability and short half-lives. Biological macromolecular drugs are typically administrated via invasive methods, e.g., intravenous or subcutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 113 publications
(125 reference statements)
0
24
0
Order By: Relevance
“…We focused on ItP as a non-invasive method for the potential intramuscular delivery of MID-35. Previously, we have demonstrated the utility of ItP for the delivery of various macromolecules, such as siRNA, liposomes and antibodies [ 27 ]. siRNA has been delivered into the skin by ItP and induced significant knocking down of the expression of target interleukin 10 mRNA.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…We focused on ItP as a non-invasive method for the potential intramuscular delivery of MID-35. Previously, we have demonstrated the utility of ItP for the delivery of various macromolecules, such as siRNA, liposomes and antibodies [ 27 ]. siRNA has been delivered into the skin by ItP and induced significant knocking down of the expression of target interleukin 10 mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that macromolecules such as siRNA and liposomes can penetrate into intercellular spaces cleaved by weak electric currents. Therefore, we concluded that ItP would promote transdermal penetration of macromolecules by cleaving intercellular junctions through activation of cell signaling pathways via Ca 2+ influx [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies devote iontophoretic drug delivery to promoting the permeation of different drugs in different pathologic conditions; salbutamol [11] and acyclovir [12] were delivered as iontophoretic drugs in early studies. At present, more kinds of drugs are delivered by iontophoresis for improving treatment effects, such as ocular drugs [13], propranolol [14], biological macromolecular drugs [15], etc. Scars can be treated with iontophoresis, in which cathodal iontophoresis enhances the delivery of sodium fluorescein across the scar skin epidermis by approximately 46 folds, meaning iontophoresis could be utilized to overcome the barrier resistance of the scar skin epidermis and treat scars regionally [16].…”
Section: Introductionmentioning
confidence: 99%